Interleukin 17 in early invasive breast cancer - Popović, Marina; Dedić Plavetić, Natalija; Vrbanec, Damir; Marušić, Zlatko; Mijatović, Davor; Kulić, Ana (Frontiers in Oncology, 2023)
Introduction Interleukin 17 (IL-17) has a key role in inflammatory responses. Increased serum concentrations of IL-17 have been reported in patients with different types of cancer. Some studies suggest antitumor activity of IL-17 while others speak in favor of its association with poorer prognosis. The lack of data on IL-17 behavior in vivo hinders the efforts to clarify the exact role of IL-17 in breast cancer patients and precludes the usage of IL-17 as potential therapeutic target. Methods The study included 118 patients with early invasive breast cancer. The serum concentration of IL-17A was measured before surgery and during adjuvant treatment and compared with healthy controls. The correlation of serum IL-17A concentration and different clinical and pathological parameters, including IL-17A expression in the corresponding tumor tissue samples, was analyzed. Results Significantly higher serum concentrations of IL-17A were found in women with early breast cancer before surgery, but also during adjuvant treatment in comparison to healthy controls. No significant correlation to tumor tissue IL-17A expression was observed. There was a significant postoperative decrease of serum IL-17A concentrations even in patients with relatively lower preoperative values. A significant negative correlation was found between serum IL-17A concentrations and the tumor estrogen receptor expression. Conclusion The results suggest that the immune response in early breast cancer is mediated by IL-17A, particularly in triple-negative breast cancer. IL-17A-mediated inflammatory response subsides postoperatively, but IL-17A concentrations remain elevated compared to the values in healthy controls, even after the removal of the tumor.